ANALISIS PENGARUH PENGANGGURAN DAN KEMISKINAN TERHADAP KRIMINALITAS DI KABUPATEN MIMIKA - Merli Latif; Siske Tontong (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to determine the influence of unemployment and poverty on crime in Mimika Regency. This is an associative study employing data collection techniques such as documentation and literature review. The data analysis tool used in this study is the Granger causality test, which is used to examine the causal or reciprocal relationship between the two research variables so that it can be determined whether the two variables statistically influence each other (a two-way or reciprocal relationship), have a unidirectional relationship, or have no relationship at all (do not influence each other). The results of the analysis indicate that unemployment and poverty do not have a causal relationship with crime. Based on the research findings, an increase in unemployment and poverty does not affect crime itself, and vice versa.